Status of women in the contexts of world religions: comparative analysis (Journal of Philosophy Culture and Political Science, 2018)
This article deals with the comparative analyses of the status of women in the context of world religions. The status In Holy Book of Christianity, and in the Buddhist tradition and the position of the woman in the Vedas and in Islam are discussed separately. Also the advantages and disadvantages of the woman’s status in every religion. The equality of men and women in the contexts of world religions are described in the article.The theme of a woman in religion has been and continues to be relevant today. So, the basic and traditional religions revere a woman for her special mission in the history of the human race, for deep spirituality and selflessness, for the divine gift of love and wisdom. The woman is first of all, mother and daughter, wife and sister, keeper of the hearth and public figure, which can be traced in the concept of the organization of the world. In general, the question of the status of women, especially in the context of religion, in every society and in all eras, was of great importance. Each religion expressed its attitude towards the role of women in the family, society, and about her rights. Accordingly, this topic is relevant and practically meaningful for modern society.Key words: Religion, Woman, woman in religion, Gender, Christianity, Buddhism, Islam.